2016
DOI: 10.1111/jai.13203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ammonia on growth, digestion and antioxidant capacity in juvenile yellow catfish Pelteobagrus fulvidraco (Richardson, 1846)

Abstract: SummaryEffects of ammonia stress on food ingestion, growth, digestion and antioxidant capacity were investigated in juvenile yellow catfish Pelteobagrus fulvidraco (Richardson) with initial body weights of 20.24 ± 0.18 g. The fish were reared in triplicate in 15 experimental tanks at a rate of 30 fish per tank for 56 days. Water was maintained at a dissolved oxygen (DO) level of over 6.2 mg L . The results show that the survival, FI, SGR, FCE, and ADC decreased significantly with an increase in total ammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Many previous investigations have proved that ammonia is a critical environmental limited factor to inhibit fish growth performance. 20,42,43 However, the underlying molecular mechanism of chronic ammonia toxicity on the growth is still unclear. This present 18,20,22,[44][45][46] As we known, the GH/IGF axis play a key part in regulating fish growth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many previous investigations have proved that ammonia is a critical environmental limited factor to inhibit fish growth performance. 20,42,43 However, the underlying molecular mechanism of chronic ammonia toxicity on the growth is still unclear. This present 18,20,22,[44][45][46] As we known, the GH/IGF axis play a key part in regulating fish growth.…”
Section: Discussionmentioning
confidence: 99%
“…20,42,43 However, the underlying molecular mechanism of chronic ammonia toxicity on the growth is still unclear. This present 18,20,22,[44][45][46] As we known, the GH/IGF axis play a key part in regulating fish growth. 25,26 A few current researches have reported that acute ammonia exposure could inhibit mRNA expression levels of GH/IGF-axis genes in fish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, hepatic MDA and PC in all experimental groups significantly increased compared with before ammonia, which suggested that acute ammonia exposure induced oxidative stress and protein damage in the liver of juvenile Wuchang bream. Elevated MDA levels have been reported in bighead carp Hypophthalmythys nobilis larvae ( Sun et al, 2012 ), sea bass ( Dicentrarchus labrax ) ( Sinha et al, 2015 ), yellow catfish ( Pelteobagrus fulvidraco ) ( Zhang et al, 2016 ) after exposure to ammonia and indicated the occurrence of oxidative stress in fish body. Significantly increased PC were also detected in the brain of mudskipper ( Boleophthalmus boddarti ) exposed to a sublethal concentration of NH 4 Cl (8 mmol/L) for 48 h ( Ching et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%